2017
DOI: 10.1016/j.urolonc.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Advances in medical imaging for the diagnosis and management of common genitourinary cancers

Abstract: Medical imaging of the three most common genitourinary (GU) cancers—prostate adenocarcinoma, clear cell renal cell carcinoma (RCC), and urothelial carcinoma of the bladder—has evolved significantly during the past decades. The most commonly used imaging modalities for the diagnosis, staging, and follow-up of GU cancers are computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET). Multiplanar multidetector CT and multiparametric MRI (mpMRI) with diffusion-weighted imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 148 publications
(142 reference statements)
0
33
0
Order By: Relevance
“…However, in a staging study of 42 patients prior to cystectomy, FDG-PET-CT detected metastases in seven patients who showed no evidence of disease on CT and bone scans [57]. A published review of six series also found a high diagnostic accuracy for metastatic lesions using FDG-PET-CT [58], and a recent review from the National Institutes of Health (Bethesda, MD, USA) concluded that FDG-PET-CT was the optimal technology in this setting [59]. Statement 2: PET-CT scanning should be included in OMD staging when considering radical treatment.…”
Section: The Role Of Positron Emission Tomography-computed Tomographymentioning
confidence: 97%
“…However, in a staging study of 42 patients prior to cystectomy, FDG-PET-CT detected metastases in seven patients who showed no evidence of disease on CT and bone scans [57]. A published review of six series also found a high diagnostic accuracy for metastatic lesions using FDG-PET-CT [58], and a recent review from the National Institutes of Health (Bethesda, MD, USA) concluded that FDG-PET-CT was the optimal technology in this setting [59]. Statement 2: PET-CT scanning should be included in OMD staging when considering radical treatment.…”
Section: The Role Of Positron Emission Tomography-computed Tomographymentioning
confidence: 97%
“…For high-grade non-muscle invasive bladder cancer (NMIBC) and muscle invasive bladder cancer (MIBC), MRI may detect and stage tumors with high sensitivity and specificity (7). mpMRI has demonstrated high diagnostic accuracy in differentiating NMIBC from MIBC and organ-confined disease from non-organ confined disease (8); exceeding that of T2 weighted imaging (T2W) or diffusion weighted imaging (DWI)-MRI used alone (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, in a staging study of 42 patients before cystectomy, FDG-PET-CT detected metastases in seven patients who showed no evidence of disease on CT and bone scans [57]. A published review of six series also found a high diagnostic accuracy for metastatic lesions using FDG-PET-CT [58], and a recent review from The National Institutes of Health, Bethesda, USA, concluded that FDG-PET-CT was the optimal technology in this setting [59].…”
Section: Statementmentioning
confidence: 99%